Introduction: The Scholarship of Teaching and Learning in Counselling Psychology - Roughley, Robert A.; Luft, Toupey; Cummings, Jill (Canadian Journal of Counselling and Psychotherapy, 2021)
Over the past 30 years, the field of counselling psychology has experienced many new insights and shifting practices into counsellor education, practitioner and faculty scholarship, and larger systems including post-secondary institutions, accreditation councils, and regulatory bodies. One of the central contributions to this expanding landscape is the Scholarship of Teaching and Learning (SoTL). In this introduction to the present special issue of Canadian Journal of Counselling and Psychotherapy, the authors outline the trends and developments in SoTL and discuss current applications of SoTL to the field of counselling psychology. They highlight the importance of these applications for moving the field of counselling forward. Each of the four articles within this special issue is described briefly through the lens of its contributions to SoTL within counselling psychology.